A proposed simplified scorecard for the linear descriptive evaluation of dairy characters of female camels (Camelus dromedarius) of the Majaheem breed - Maurizio Dioli; Mostafa Nasef; Bruce James Braithwaite; Umar Rehman (Frontiers in Animal Science, 2023)
The camel (Camelus dromedarius) holds significant importance as a valuable livestock species for milk production. Consequently, there is an increasing need to enhance attitudes toward increasing camel milk production by selectively breeding camels with desirable milk production attributes. The Majaheem camels have gained recognition for their favorable milk production traits. However, there is currently a lack of rational and modern tools to aid in the evaluation of Majaheem camels, specifically in terms of their milk production capabilities. To address this deficiency and provide guidance to camel breeders for the effective evaluation and selection of superior milk-producing Majaheem camels, a breed linear scorecard is proposed in line with that adopted for Holstein–Friesian milking cattle. However, the scorecard has been simplified and adapted to the phenotypic characteristics of the Majaheem camel breed.